Rencana Pemasaran Klinik Eksekutif Rumah Sakit Hermina Depok dengan Pendekatan Balanced Scorecard - Nurpeni, Evi Febrina (UI Scholars Hub, 2015)
Executive Clinic is a new differention product of Hermina Depok Hospital to serve out patient as part of enhancement of services quality and increasing revenue of the hospital. Since the very beginning of the establishment of this clinic in December 2012, performance of the clinic has not yet reached the expected target. This thesis covers marketing plan for this Executive Clinic using Balanced Scorecard (BSC) approach. The results of the research showas Executive Clinic has market in Depok, but this new product has not popular already because market does not well know all the facilities in Executive Clinic. CDMG decided that marketing plan focused in market penetration with marketing mix and promotion mix also increasing the service quality. BSC indicators were used for measureing the achievement of every unit in the organization.